1991
DOI: 10.1093/bja/66.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of I.V. Anaesthesia With Propofol on Drug Distribution and Metabolism in the Dog

Abstract: We have studied the effect of i.v. anaesthesia with propofol in the emulsion (Intralipid) formulation on drug distribution and metabolism in six dogs using dual-route administration of propranolol as a model compound. Each dog was studied on two consecutive days: day 1 awake and day 2 during propofol anaesthesia (6 mg kg-1 followed by an infusion of 0.8 mg kg-1 min-1). Propofol anaesthesia was associated with reduced intrinsic clearance by 40% (P less than 0.05) but no significant difference in systemic cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…, ), administration of the two drugs together can be expected to slow elimination and increase plasma drug concentrations (Perry et al. ), altering the pharmacokinetics of both agents. There are several reports of benzyl alcohol toxicity in cats due to administration of substances containing this preservative (Bedford & Clarke , ; Humphreys ; Cullison et al.…”
Section: Introductioncontrasting
confidence: 99%
“…, ), administration of the two drugs together can be expected to slow elimination and increase plasma drug concentrations (Perry et al. ), altering the pharmacokinetics of both agents. There are several reports of benzyl alcohol toxicity in cats due to administration of substances containing this preservative (Bedford & Clarke , ; Humphreys ; Cullison et al.…”
Section: Introductioncontrasting
confidence: 99%
“…It is therefore feasible to apply this model during an exploratory laparotomy to assess liver function when extensive cirrhosis or neoplastic metastasis is found, particularly following substantial hepatic resection. As a range of conditions are known to affect hepatic drug metabolism, including anaesthetic agents used to perform surgery (Perry et al. , 1991), it is also a useful experimental model to specifically investigate drug extraction and metabolism by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the model presented in this study may be a useful tool to study a range of conditions that are known to affect hepatic drug metabolism, including anaesthetic agents used prior to performing surgery (Perry et al. , 1991).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Propofol interacts with drugs such as propranolol, by changing plasma protein binding and affecting its drug disposition. 11 The enzymatic degradation of sufentanil and alfentanil in the liver may be inhibited by propofol. 1 2 Previous investigations in the rat and in our human liver model demonstrated that interference in oxidative metabolism by propofol was mainly through inhibition of the cytochrome P450-dependent monooxygenase system.…”
Section: Discussionmentioning
confidence: 99%